2004
DOI: 10.1051/apido:2003063
|View full text |Cite
|
Sign up to set email alerts
|

Nosema apis infection in worker and queen Apis mellifera

Abstract: -Worker and queen honey bees were fed individually with Nosema apis spores in sucrose solution and then returned to cages containing several hundred of their worker bee nestmates. After 3 to 7 days, the workers and queens that had been fed spores were sacrificed. Worker and queen ventriculi were removed and examined for spores by light microscopy, and DNA was extracted. The DNA was subjected to amplification with polymerase chain reaction, using primer sequences specific to N. apis DNA. The PCR analysis was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 14 publications
3
31
0
1
Order By: Relevance
“…The cited authors have suggested that the above resulted from the absence of sporulation and spore deposition in the intestine for long periods of time. Undigested spores have flexible walls, and they are resistant to DNA extraction (Webster et al 2004). The results of this study support the above theory.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The cited authors have suggested that the above resulted from the absence of sporulation and spore deposition in the intestine for long periods of time. Undigested spores have flexible walls, and they are resistant to DNA extraction (Webster et al 2004). The results of this study support the above theory.…”
Section: Discussionsupporting
confidence: 86%
“…The above authors investigated 78 Eastern honey bee specimens to conclude that 71% samples were invaded by Nosema ceranae, 19% samples were affected by a mixed infection, and 31% samples -by Nosema apis spores (Chen et al 2009b). Webster et al (2004) studied worker bees in late autumn to determine their ability to transfer parasitic spores to queen bees. Although Nosema apis spores were observed under a light microscope in specimens infected with nosemosis as well as in the intestines of worker bees and queen bees, they were not found in DNA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In worker bees, microsporidian infections inhibit the development of hypopharyngeal glands that secrete royal jelly, thus disrupting the feeding of queens and the brood [5]. N. apis infections shorten the lifespan of worker bees and queen bees, leading to ovarian damage and infertility in queens [6]. The disease lowers honey production and can reduce brood by even 50%.…”
Section: Introductionmentioning
confidence: 99%
“…While honey bees are hosts to a wide variety of parasites and pathogens (Schmid-Hempel, 1998), only a subset tend to infect queen bees. The more notable parasites of queens are tracheal mites Acarapis woodi (Burgett and Kitprasert, 1992;Camazine et al, 1998;Villa and Danka, 2005), the gut protozoan Nosema apis (Webster et al, 2004(Webster et al, , 2008 and, presumably, N. ceranae (Higes et al, 2006(Higes et al, , 2008. Moreover, queens may be infected with numerous viruses (Chen et al, 2005;Yang and Cox-Foster, 2005), including acute bee paralysis virus (ABPV), chronic bee paralysis virus (CBPV), black queen cell virus (BQCV), deformed wing virus (DWV), Kashmir bee virus (KBV), sacbrood virus (SBV), and Israeli acute paralysis virus (IAPV).…”
Section: Introductionmentioning
confidence: 99%